Skull-femoral traction after posterior release for correction of adult severe scoliosis: efficacy and complications - Jun Qiao; Lingyan Xiao; Leilei Xu; Zhen Liu; Xu Sun; Bangping Qian; Zezhang Zhu; Yong Qiu (BMC Musculoskeletal Disorders, 2018)
Abstract Background It is a great challenge for spine surgeons to correct severe rigid scoliosis. We developed a three- staged correction (one stage posterior release and screw placement, two stage skull-femoral traction and three stage posterior instrumentation) for adult severe scoliosis. The objective of this study is to investigate safety and efficacy of a three- staged correction for adult severe scoliosis. Methods A retrospective review was performed for patients with severe scoliosis receiving three- staged correction (one stage posterior release and screw placement, two stage skull-femoral traction and three stage posterior instrumentation) from June 2001 to October 2014. The inclusion criteria were as follows: [1] age more than 18 years; [2] main curve larger than 90°; [3] a minimum 2-year follow-up. Patients were excluded if they had a history of surgery or anterior release or receiving three column osteotomies. Results A total of 63 patients were included (37 female and 26 male), with a mean age of 22.7 years (range: 18–30 years) and follow-up of 42.6 months (range: 24–108 months). The aetiology was congenital in 27 patients, neuromuscular in 18, idiopathic in 11, neurofibromatosis-1 in 4 and Marfan syndrome in 3. The mean traction weight was 28.4 kg (range: 18–32 kg), equal to 57.2% of patients’ body weight (range: 42.7–72.3%). The mean traction time was 22.7 days (range: 12–44 days). Postoperative correction rate was 55% (range: 38–78%) for scoliosis and 51% (range: 32–75%) for kyphosis. Contribution of traction to correction was 51% (range: 36–70%) for scoliosis and was 43% (range: 34–55%) for kyphosis. Conclusions Three- staged correction (one stage posterior release and screw placement, two stage skull-femoral traction and three stage posterior instrumentation) could effectively correct adult severe scoliosis. The incidence of complications of skull-femoral traction was not low, but transient and could be successfully managed.